Penerimaan Pengungsi Afghanistan oleh Korea Selatan pada Tahun 2021 Melalui Operation Miracle - Ramadani, Layli; Afriani Sinulingga, Anita; Cory, Silvi (Hubungan Internasional Universitas Andalas, 2023)
South Korea is one of the countries that ratified the 1951 Refugee Convention in 1992 and implemented it into domestic regulations in 2013. Even though it has been ratified and implemented, the rate of acceptance of refugees in South Korea is very low. In 2020 the refugee acceptance rate is less than two percent of the number of incoming asylum applications. South Korea appears to have implemented a policy that is closed to refugees as seen from one of the policies for returning refugees directly which is not in line with the provisions of the 1951 Refugee Convention. But in 2021, the government adopt a more hospitable policy towards refugees originating from Afghanistan. This study aims to explain the factors that influence the acceptance of Afghan refugees by South Korea in 2021. This research is analyzed using the concept of foreign policy change by Spyros Blavoukos and Dimitris Bourantonis. This study used a qualitative research methodology and a descriptive-analytical type of research. Based on the concept used, the first factor affecting the acceptance of Afghan refugees by South Korea in 2021 is the domestic structural parameter influenced by the power of progressive parties in the legislature and executive and the existence of a network of advocacy groups. Second, international structural parameters influenced by the United States' encouragement of South Korea, and the role of the UNHCR in encouraging the acceptance of Afghan refugees.